Kedudukan Putusan Mahkamah Konstitusi Dalam Hukum Ketenagakerjaan (Kajian Terhadap Putusan Mahkamah Konstitusi No. 37/PUU-IX/2011) - Suparto, Suparto; Zulkifli, Zulkifli (UI Scholars Hub, 2022)
Law Number 13 of 2003 concerning Manpower is one of the laws that is subjected to a judicial review to the Constitutional Court (MK). One of the reasons for filing a judicial review is that the application of Article 155 paragraph (2) has the potential to create legal uncertainty, given the absence of a clear interpretation of the clause